Analysis of continuous descent operations (CDO) with three-dimensional (3D) radar display - Tay, Jolyn Si Ying (2018)
The volume of global air traffic has been increasing rapidly throughout the years and several strategies have been implemented to accommodate the growth and also to deliver operational benefits. One of the strategies implemented is Continuous Descent Operations (CDO). Under this operation, the arriving aircraft will be descending continuously to the greatest extent possible hence increasing the efforts needed for the Air Traffic Controllers (ATCOs) to ensure separation between aircraft. Therefore, to assist the ATCOs in using CDO, the conventional 2-Dimensional (2D) planar display is suggested to be used together with a 3-Dimensional (3D) planar display for better visualisation. Since 3D planar display is not widely used in Air Traffic Control (ATC), the objective of this project is to see the effectiveness of 3D display for CDO. A real-time simulation to mimic the approach scenario is designed for the ATCOs to operate to assess the relevant key performance of the operation and the human factors on using 3D display for CDO. Extensive literature reviews have also been conducted to understand CDO, 2D and 3D air traffic visualisation and human factors study in air-traffic control.